The study of optimum ratio of micro size of pofa as a cement replacement - Mohammad Zulfazrin, Badrul Munir (2014)
Malaysia is the world's leading producer of palm oil. However, the advancement of the agriculture sector also leads to some bad effect especially to environment. Palm Oil Fuel Ash (POFA) is one of the by-products that produce from the combustion of the solid wastage that produced in palm oil factory. POFA had an ability to become the cement replacement in concrete. In order to find the optimum ratio of POFA used in concrete, some laboratory tests are conducted to determine the performance of POFA concrete in terms of workability, strength and durability. The result showed that POFA concrete had a lower workability compared to the control concrete G25. The compressive strength of the POFA concrete also lower compared to the conventional concrete. However, the flexural strength of concrete incorporated with 10% POFA was higher than the conventional G25 concrete. It means that 10% is the optimum ratio of POFA to substitute cement in concrete. In terms of durability, POFA concrete had a lower water penetration than conventional concrete G25. The result clarify that POFA had an ability to substitute 10% content of cement and improve the performance of concrete. For the suggestion, future details study of POFA in concrete should be carry out. Furthermore, the lower penetration of water in POFA concrete made it suitable to be used for the building that requires low water permeability of water like seaside construction.